Physical activity of early stage melanoma survivors - J.K. Robinson, MD (Wolters Kluwer, 2019)
Background: Early stage melanoma survivors are typically otherwise healthy adults with a median age of 56.5 years for women at the time of diagnosis. Women have a projected lifespan of 20 to 30 additional years during which they should be able to enjoy and benefit from leisure outdoor physical activities while limiting their risk of a second melanoma from unprotected sun exposure. Objective: This study evaluated the physical activity of melanoma survivors before their diagnosis of melanoma as well as 2 to 3 months and 12 months after surgical resection. Methods: Participants in this observational study were early stage melanoma survivors (Stage 0-1A) who were surgically treated for melanoma within the last 6 months. Participants completed three online surveys (Leisure Time Exercise Questionnaire) that estimated their physical activity 2 to 3 months prior to the diagnosis with melanoma as well as 2 to 3 months and 12 months after surgery. Results: All 75 participants were non-Hispanic white, and 38 of 75 participants (50.6%) were women. The median age of this urban/suburban Midwest population was 52 years. Prior to their diagnosis, all melanoma survivors were active, and 55% of women reported vigorous leisure physical activity. Two to three months after surgery, 11 of 38 women (30%) were inactive and 31% were inactive at 12 months. At 12 months after surgery, inactivity was positively correlated with older age (61-80+ years; F1050 = 15.38; p < .001) and being a woman (0.05; F1050 = 11.02; p < .01). Conclusion: Dermatologists are in a position to promote a healthy lifestyle for melanoma survivors, especially older women who can be expected to live many more years and may restrict leisure outdoor physical activity to comply with sun protection recommendations. When considering the overall health of older, female melanoma survivors, dermatologists may recommend they walk with a friend at any time of the day while wearing a hat, protective clothing, and sunscreen on exposed skin. Keywords: melanoma, physical activity, inactivity, healthy lifestyle